Characterization of children submitted to cardiac surgery that developed surgical site infection (Estima – Brazilian Journal of Enterostomal Therapy, 2020)
Objective: Characterize the clinical and surgical profile of children undergoing cardiac surgery who developed surgical site infection in a public hospital in the city of Fortaleza, Ceará. Methods: Descriptive research with a quantitative approach, developed in a pediatric cardiology unit, with data collected from April to June 2018. The study sample consisted of 26 children with surgical wound infection in the year 2017. Results: There were none gender prevalence; the weight range varied from 3 to 6 kg (42.3%) and neonates had a prevalence of 38%. Corrective surgeries represented 88% of the total; the surgical time varied from 2 to 6 hours (38%); 70% of the children were submitted to cardiopulmonary bypass with the predominant time of 90 to 120 minutes (27%); the diagnosis of infection was made between 4 and 6 days after the procedure. There was prophylactic antibiotic coverage in 88% and skin preparation in 92% of children. Conclusion: Characterizing the clinical-surgical profile of children undergoing cardiac surgery becomes essentialfor decision-making in the care processes of nurses, emphasizing the findings as a basis for the development of strategies for theprevention of surgical site infection in this clientele.